La «Guía de Principios sobre Responsabilidad Social de las Empresas» elaborada por el Comité Jurídico Interamericano de la OEA - Novak Talavera, Fabián (2014)
This paper presents the grounds that supported the Inter-AmericanJudicial Committee of the OAS to make and pass the “Guide of Principles on Corporative Social Responsibility in the Human Rights and Environmentareas in America» in 2013.